Folinic acid and autism spectrum disorder in children: A systematic review and meta-analysis of two double-blind randomized placebo-controlled trials - Farida Anggraini Soetedjo; Johanes Aprilius Falerio Kristijanto; Fara Disa Durry (AcTion: Aceh Nutrition Journal, 2025)
Folic acid is a synthetic vitamin B9 that plays an important role in folate metabolism, including the synthesis of DNA and RNA, and epigenetic methylation. These processes are essential for the development of the nervous system. Impaired folate metabolism contributes to the pathophysiology of ASD through the dysregulation of neurochemical and epigenetic processes. This meta-analysis aimed to evaluate the efficacy of folinic acid in alleviating ASD symptoms.  Methods: Review Manager Software. Searches were conducted in PubMed, Science Direct, and Cochrane based on studies published in the last five years (2018-2023), with inclusion criteria of RCTs and exclusion of observational studies and non-English articles. Fixed-effects analysis was used because no heterogeneity was observed. Results: Two studies (n= 103) evaluated the effect of folinic acid on reducing ASD symptoms. Symptoms were assessed using the aberrant behavior checklist. The pooled mean difference was -0,66, with a 95% confidence interval ranging from -1,22 -0,10. The results showed statistical significance, with a p-value of 0,02. However, this analysis used only two studies with small sample sizes and modest mean differences. In conclusion, folinic acid administration has the potential to reduce ASD symptoms in children. Further research with a larger sample size is needed to generalize the clinically meaningful results.